The human beta-globin locus activation region alters the developmental fate of a human fetal globin gene in transgenic mice. - Enver, T (1989)
We linked a 3.3-kilobase fragment containing the entire A gamma-globin gene together with 1.3 kilobases of 5' flanking and 0.37 kilobase of 3' flanking DNA to a 2.5-kilobase fragment containing four of the developmentally stable hypersensitive sites normally located in the 5' region of the human beta-globin locus. This construct was injected into fertilized mouse eggs, and its expression was analyzed in the primitive and definitive erythroid cells, as well as the brain of 14-day embryos. All six transgenic individuals that contained intact copies of the construct expressed the transgene in an erythroid-specific fashion. Expression was observed in both primitive and definitive erythroid cells. This is in marked contrast to previous transgenic mice experiments using the same A gamma-globin gene fragment in isolation, where expression was restricted to primitive erythroid cells. Our results show that the region containing the developmentally stable globin locus hypersensitive sites changes the developmental stage specificity of a human fetal globin gene in transgenic mice. These observations imply that sequences additional to those used here are involved in the developmental control of fetal globin gene expression in vivo. The ability to express fetal globin in adult erythroid cells allows one to consider using fetal globin genes for gene therapy of sickle cell disease.